Искусство чтения. Как понимать книги - Фостер Томас (Манн, Иванов и Фербер, 2015)
Экземпляры: СБ (201506) / Инвентарный номер: 51248 / Цена: 619.96 / Сис.шифр: 83.3(0) / Авт.знак: Ф 81 / ГРНТИ: 17 / ББК: 83.3(0)11